sj-pdf-2-smo-10.1177_2050312120973483 – Supplemental material for Disparities of perceived wellness by smoking and professional status among young individuals in Brasov, Brasov County, Romania - Fan, Hao; Gao, Xiang; Wang, Haiping; Idomir, Mihaela; Rogozea, Liliana; Cazan, Ana-Maria; Bidulescu, Aurelian; Badea, Mihaela (SAGE Journals, 2020)
Supplemental material, sj-pdf-2-smo-10.1177_2050312120973483 for Disparities of perceived wellness by smoking and professional status among young individuals in Brasov, Brasov County, Romania by Hao Fan, Xiang Gao, Haiping Wang, Mihaela Idomir, Liliana Rogozea, Ana-Maria Cazan, Aurelian Bidulescu and Mihaela Badea in SAGE Open Medicine